Achievement motivation among supervisors in youth and sports directorates - BOURAGdA, Messaoud; Mirouh, Abdelouahab; guermat, nori (sports creativity, 2025)
This study aims to identify the correlation between achievement motivation among supervisors with 10-20 years of professional experience and supervisors with 1-10 years of professional experience. It also examines the differences in achievement motivation between supervisors with 10-20 years of professional experience and supervisors with 1-10 years of professional experience.